Seafood poisoning symptom, treatment and prevention - Murtaza Mustafa; Teruaki Yoshida; Zarinah Waheed; Mohd Yusof Ibrahim; Mohammad Illzam Elahee; Shahjee Hussain; Sharifa Mariam Uma Abdullah; Mehvish Muhammad Hanif (Borneo Marine Research Institute, 2018)
Food related disease or food poisoning is prevalent worldwide and is associated with high mortality. It can be caused by bacteria, viruses, parasites, enterotoxins, mycotoxins, chemicals, histamine poisoning (scombroid) ciguatera and harmful algal bloom (HAB). Illness can also result by red tide while breathing in the aerosolized brevitoxins (i.e. PbTx or Ptychodiscus toxins). Bacterial toxin food poisoning can affect within 1-6 hours and 8-16 hours, and illness can be with or without bloody diarrhea. The common symptoms of food poisoning include abdominal cramps, vomiting and diarrhea. Diagnosis includes examination of leftover food, food preparation environment, food handlers, feces, vomitus, serum and blood. Treatment involves oral rehydration, antiemetic, and anti-peristaltic drugs. Antimicrobial agents may be needed in the treatment of shigellosis, cholera, lifesaving invasive salmonellosis and typhoid fever. Proper care in handling and cooking is important to prevent any food borne diseases